Epidemiology of taeniosis/cysticercosis in Europe, a systematic review : Western Europe - Laranjo-Gonzalez, Minerva; Devleesschauwer, Brecht; Trevisan, Chiara; Allepuz, Alberto; Sotiraki, Smaragda; Abraham, Annette; Afonso, Mariana Boaventura; Blocher, Joachim; Cardoso, Luis; Correia da Costa, Jose Manuel; Dorny, Pierre; Gabriel, Sarah; et al. (Parasites & Vectors, 2017)
Background: Taenia solium and Taenia saginata are zoonotic parasites of public health importance. Data on their occurrence in humans and animals in western Europe are incomplete and fragmented. In this study, we aimed to update the current knowledge on the epidemiology of these parasites in this region. Methods: We conducted a systematic review of scientific and grey literature published from 1990 to 2015 on the epidemiology of T. saginata and T. solium in humans and animals. Additionally, data about disease occurrence were actively sought by contacting local experts in the different countries. Results: Taeniosis cases were found in twelve out of eighteen countries in western Europe. No cases were identified in Iceland, Ireland, Luxembourg, Norway, Sweden and Switzerland. For Denmark, Netherlands, Portugal, Slovenia, Spain and the UK, annual taeniosis cases were reported and the number of detected cases per year ranged between 1 and 114. Detected prevalences ranged from 0.05 to 0.27%, whereas estimated prevalences ranged from 0.02 to 0.67%. Most taeniosis cases were reported as Taenia spp. or T. saginata, although T. solium was reported in Denmark, France, Italy, Spain, Slovenia, Portugal and the UK. Human cysticercosis cases were reported in all western European countries except for Iceland, with the highest number originating from Portugal and Spain. Most human cysticercosis cases were suspected to have acquired the infection outside western Europe. Cases of T. solium in pigs were found in Austria and Portugal, but only the two cases from Portugal were confirmed with molecular methods. Germany, Spain and Slovenia reported porcine cysticercosis, but made no Taenia species distinction. Bovine cysticercosis was detected in all countries except for Iceland, with a prevalence based on meat inspection of 0.0002-7.82%. Conclusions: Detection and reporting of taeniosis in western Europe should be improved. The existence of T. solium tapeworm carriers, of suspected autochthonous cases of human cysticercosis and the ...